Education for All? A Nationwide Audit Study of School Choice - Peter Bergman; Isaac McFarlin (Institute of Labor Economics (IZA), 2020)
School choice may allow schools to impede access to students perceived as costlier to educate. To test this, we sent emails from fictitious parents to 6,452 charter schools and traditional public schools subject to school choice in 29 states and Washington, D.C. The fictitious parent asked whether any student is eligible to apply to the school and how to apply. Each email signaled a randomly assigned attribute of the child. We find that schools are less likely to respond to inquiries from students with poor behavior, low achievement, or a significant special need. Lower response rates to students with this special need are driven by charter schools. Otherwise, these results hold for traditional public schools, high value-added schools, including high-value added, urban charter schools.
Keywords: I20; I21; I24; I28; 330; school choice; discrimination; audit study; experiment